Anomalous Hall Conductivity and Nernst Effect of the Ideal Weyl Semimetallic Ferromagnet EuCd2As2 - Subhajit Roychowdhury; Mengyu Yao; Kartik Samanta; Seokjin Bae; Dong Chen; Sailong Ju; Arjun Raghavan; Nitesh Kumar; Procopios Constantinou; Satya N. Guin; Nicholas Clark Plumb; Marisa Romanelli; et al. (Advanced Science, 2023)
Abstract Weyl semimetal is a unique topological phase with topologically protected band crossings in the bulk and robust surface states called Fermi arcs. Weyl nodes always appear in pairs with opposite chiralities, and they need to have either time‐reversal or inversion symmetry broken. When the time‐reversal symmetry is broken the minimum number of Weyl points (WPs) is two. If these WPs are located at the Fermi level, they form an ideal Weyl semimetal (WSM). In this study, intrinsic ferromagnetic (FM) EuCd2As2 are grown, predicted to be an ideal WSM and studied its electronic structure by angle‐resolved photoemission spectroscopy, and scanning tunneling microscopy which agrees closely with the first principles calculations. Moreover, anomalous Hall conductivity and Nernst effect are observed, resulting from the non‐zero Berry curvature, and the topological Hall effect arising from changes in the band structure caused by spin canting produced by magnetic fields. These findings can help realize several exotic quantum phenomena in inorganic topological materials that are otherwise difficult to assess because of the presence of multiple pairs of Weyl nodes.